2020
DOI: 10.1101/2020.06.24.169938
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Systematic evaluation of parameters for genome-scale metabolic models of cultured mammalian cells

Abstract: 10Genome-scale metabolic models describe cellular metabolism with mechanistic detail. 11Given their high complexity, such models need to be parameterized correctly to yield 12 accurate predictions and avoid overfitting. Effective parameterization has been well-13 studied for microbial models, but it remains unclear for higher eukaryotes, including 14 mammalian cells. To address this, we enumerated model parameters that describe key 15 features of cultured mammalian cells -including cellular composition, biopro… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 102 publications
0
10
0
Order By: Relevance
“…These results are specific to the use of biomass objective function. Schinn et al [34] reported that the objective function has a big impact on the prediction accuracy and the biomass objective function was correlated with poor predictions. A suggested alternative was minimization of cytosolic NADPH regeneration, which was correlated with good predictions.…”
Section: Discussionmentioning
confidence: 99%
“…These results are specific to the use of biomass objective function. Schinn et al [34] reported that the objective function has a big impact on the prediction accuracy and the biomass objective function was correlated with poor predictions. A suggested alternative was minimization of cytosolic NADPH regeneration, which was correlated with good predictions.…”
Section: Discussionmentioning
confidence: 99%
“…We used a previously described metabolic network model that is tailored to the investigated CHO clones (Schinn et al, 2020). Experimental measurements for clone and culture day were used to constrain model reactions for biomass production, monoclonal antibody secretion and consumption of glucose, lactate, glutamate, and glutamine.…”
Section: Methodsmentioning
confidence: 99%
“…We used a previously described metabolic network model that is tailored to the investigated CHO clones (Schinn et al, 2020). Experimental et al, 2014) and COBRApy (Ebrahim et al, 2013).…”
Section: Metabolic Network Modelingmentioning
confidence: 99%
“…We sought to predict these diverse consumption behaviors using a tailored model of CHO metabolism (Schinn et al, 2020). As input information, we utilized the following routinely measured industrial bioprocess data: (1) viable cell density and titer measurements, from which growth rate and specific productivity are calculated (Methods, equation 1), and (2) bioreactor concentrations of glucose, lactate, glutamate and glutamine, from which their respective consumption rates are calculated.…”
Section: Short Communicationmentioning
confidence: 99%